2015
DOI: 10.17772/gp/59024
|View full text |Cite
|
Sign up to set email alerts
|

Rapid diagnostics of the most frequent fetal aneuploidies with QF-PCR method – study of 100 cases

Abstract: Streszczenie

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
2
1
0
Order By: Relevance
“…Additionally, one Turner mosaic sample was revealed to be normal in QF-PCR testing. This result is in accordance with the literature and can be explained by lower rates of mosaic cells (less than 15%) 19-22.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Additionally, one Turner mosaic sample was revealed to be normal in QF-PCR testing. This result is in accordance with the literature and can be explained by lower rates of mosaic cells (less than 15%) 19-22.…”
Section: Discussionsupporting
confidence: 93%
“…This difference in the prevalence of aneuploidy could be explained by the indication of the karyotype that was primarily due to fetal malformation in our study. Łaczmańska et al 19 analyzed 100 samples of amniotic fluid and obtained compatibility in 95 cases (95%), which agrees with our study due to the higher number of chromosomal abnormalities, which were found in 28 pregnancies (29.5%).…”
Section: Discussionsupporting
confidence: 91%
“…Lildballe et al analyzed 2550 samples from chorionic villus sampling (CVS) and amniotic fluid from high-risk pregnancies and reported positive and negative predictive values greater than 99.8% [6]. Łaczmańska et al [7] analyzed 100 samples of amniotic fluid and reported concordance in 95 cases (95%). Rostami et al [8] reported 4058 samples analyzed for QF-PCR with a concordance of 98.59%.…”
Section: Discussionmentioning
confidence: 99%